Institutional abuse – characteristics of victims, perpetrators and organsations: a systematic review - Kamavarapu, Y.S.; Ferriter, Michael; Morton, S.; Völlm, Birgit (Elsevier, 2016)
Abuse of vulnerable adults in institutional settings has been reported from various countries; however, there has been no systematic review of the characteristics of the victims and their Q3 abusers. Our aim was to identify and synthesise the literature on victims and perpetrators of abuse in institutions and the characteristics of the institutions where abuse occurs in order to inform interventions to prevent such abuse.